2009
DOI: 10.1097/hjh.0b013e3283186994
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effect of French maritime pine bark extract (Flavangenol): possible involvement of endothelial nitric oxide-dependent vasorelaxation

Abstract: Thus, it seems likely that the antihypertensive effect of Flavangenol is attributable to both its antioxidative property-related protective effects against endothelial dysfunction and the endothelium-dependent vasorelaxant effect, which is mediated by endothelial nitric oxide synthase activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…PYC possesses a potent endothelium-dependent vasorelaxant activity on rat aortic rings in vitro, and vasorelaxation is suppressed by pretreatment with a nonselective nitric oxide (NO) synthase (NOS) inhibitor (Fitzpatrick et al, 1998), suggesting that PYC-induced endothelium-dependent vasorelaxation is associated with NOS. Indeed, a report in 2009 demonstrated that PYC-induced endothelium-dependent vasorelaxation was mediated by the endothelial NOS-NO-soluble guanylate cyclase signaling system (Kwak et al, 2009). Other studies involving hypertensive patients showed that dietary PYC supplementation decreases plasma endothelin-1 concentrations, whereas NO metabolite levels in plasma tend to increase, suggesting PYC has beneficial effects on endothelial function in hypertensive patients (Liu et al, 2004).…”
Section: Organ Protective Effects Of Pbe Cardiovascular Protectionmentioning
confidence: 99%
“…PYC possesses a potent endothelium-dependent vasorelaxant activity on rat aortic rings in vitro, and vasorelaxation is suppressed by pretreatment with a nonselective nitric oxide (NO) synthase (NOS) inhibitor (Fitzpatrick et al, 1998), suggesting that PYC-induced endothelium-dependent vasorelaxation is associated with NOS. Indeed, a report in 2009 demonstrated that PYC-induced endothelium-dependent vasorelaxation was mediated by the endothelial NOS-NO-soluble guanylate cyclase signaling system (Kwak et al, 2009). Other studies involving hypertensive patients showed that dietary PYC supplementation decreases plasma endothelin-1 concentrations, whereas NO metabolite levels in plasma tend to increase, suggesting PYC has beneficial effects on endothelial function in hypertensive patients (Liu et al, 2004).…”
Section: Organ Protective Effects Of Pbe Cardiovascular Protectionmentioning
confidence: 99%
“…In addition, they found also that the oligomeric (from dimers up to heptamers) proanthocyanidin fraction obtained by fractionation of PBE by Sephadex LH-20 liquid chromatography is mainly responsible for the PBE-induced vasorelaxation, although its mechanisms were not elucidated. On the other hand, our study demonstrated that Flavangenolinduced endothelium-dependent vasorelaxation was mediated by the eNOS -NO -soluble guanylate cyclase (sGC) signaling system (17). Flavangenol-induced vasorelaxation was accompanied by the increased expression of phosphorylated-eNOS (Ser 1177 ) protein without affecting total eNOS protein level.…”
Section: Enhancement Of Nos System By Flavangenolmentioning
confidence: 73%
“…These antioxidative properties may be at least partly contributive to its protective effects against various cardiovascular diseases because increased oxidative stress is one of the major causal factors for the development of hypertension as described above (15,16). In fact, our recent study has shown that the development of DOCA-salt-induced hypertension was significantly suppressed by feeding a Flavangenolcontaining diet (17). We have reported also that O 2 − production in aortic segments tended to increase in the normal diet-fed DOCA-salt rats, but Flavangenol supplementation completely suppressed this augmentation.…”
Section: Antioxidative Effects Of Flavangenol In Hypertensionmentioning
confidence: 96%
“…Treatment with the diet of FG or ibuprofen was started at the beginning of induction. The concentrations of FG and ibuprofen diets were determined by other previous experiments, such as the effects on atherosclerosis ( 12 ) and hypertension ( 19 ), and our recent experiment ( 8 ).…”
Section: Animalsmentioning
confidence: 99%